Earnings signals in fixed-price and Dutch auction self-tender offers - Lie, E (Journal of Financial Economics, 1998)
Studies by Vermaelen (1981) and others indicate that the positive excess stock returns around self-tender offer announcements are the result of a signal of future earnings improvements. Comment and Jarrell (1991), Lee, Mikkelson and Partch (1992) and Persons (1994) argue that the signal in fixed-price self-tender offers should be stronger than the signal in Dutch auction self-tender offers. This study tests whether the earnings improvement following fixed-price self-tender offers is greater than that following Dutch auction self-tender offers. We find some evidence that earnings improve following both types of self-tender offers. However, we find no difference in earnings improvement between the two types of offers.